An uncertain future, deep uncertainty, scenarios, robustness and adaptation: How do they fit together?. (July 2016) - Maier, H.R.; Guillaume, J.H.A.; van Delden, H.; Riddell, G.A.; Haasnoot, M.; Kwakkel, J.H.
Abstract: A highly uncertain future due to changes in climate, technology and socio-economics has led to the realisation that identification of "best-guess" future conditions might no longer be appropriate. Instead, multiple plausible futures need to be considered, which requires (i) uncertainties to be described with the aid of scenarios that represent coherent future pathways based on different sets of assumptions, (ii) system performance to be represented by metrics that measure insensitivity (i.e. robustness) to changes in future conditions, and (iii) adaptive strategies to be considered alongside their more commonly used static counterparts. However, while these factors have been considered in isolation previously, there has been a lack of discussion of the way they are connected. In order to address this shortcoming, this paper presents a multidisciplinary perspective on how the above factors fit together to facilitate the development of strategies that are best suited to dealing with a deeply uncertain future. Highlights: Integrated view of concepts for dealing with a highly uncertain future in modelling. Role of multiple plausible futures amongst other paradigms for modelling the future. Relation of multiple plausible futures to deep, local/global uncertainty and VUCA. Overview of how different scenario approaches help to identify plausible futures. Factors affecting static and adaptive approaches to robustness to multiple futures.